IMPLEMENTASI 7 KEBIASAAN ANAK INDONESIA HEBAT DALAM PEMBENTUKKAN KARAKTER DISIPLIN SISWA SEKOLAH DASAR (Studi Kasus di SDN 2 Sukatani Kabupaten Purwakarta) - Waska Wasta; Aida Latifah; Eneng Robi’ah; Leli Nurlaeli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The formation of students’ disciplinary character is a fundamental objective of elementary education and should be systematically integrated into school culture and management. In practice, however, schools often face challenges such as inconsistent disciplinary behavior among students, limited habituation continuity, and differences in character education practices between school and home environments. One strategic effort to address these challenges is the implementation of the 7 Habits of Great Indonesian Children as a structured and sustainable character habituation program designed to foster positive daily behaviors. This study aims to describe and analyze the implementation of the 7 Habits of Great Indonesian Children in shaping the disciplinary character of elementary school students at SDN 2 Sukatani, Purwakarta Regency. The research focuses on planning, organizing, implementation, and evaluation processes, as well as identifying supporting and inhibiting factors in the program’s implementation. A qualitative approach with a case study design was employed in this research. Data were collected through observation, in-depth interviews, and documentation. The research informants included the school principal, teachers, students, and parents. Data validity was ensured through source and technique triangulation. Data analysis was conducted using descriptive qualitative methods involving data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the 7 Habits of Great Indonesian Children at SDN 2 Sukatani has been carried out in a planned, organized, and sustainable manner. The program effectively contributes to the development of students’ disciplinary character through consistent positive habituation, supported by strong school leadership, active teacher involvement, parental participation, and a conducive school environment. Therefore, the implementation of the 7 Habits of Great Indonesian Children plays a significant role in strengthening disciplinary character education in elementary schools.